Effect of vitamin D supplementation on disease activity (SLEDAI) and fatigue in Systemic Lupus Erythematosus patients with hipovitamin D: An Open Clinical Trial - Rifa’i, Achmad; Kalim, Handono; Kusworini, Kusworini; Wahono, Cesarius Singgih (Indonesian Rheumatology Association, 2016)
Background : Low level of vitamin D impact the disease activity and the degree of fatigue in SLE patients. This study aims to determine the effect of vitamin D supplementation on disease activity and fatigue condition in Systemic Lupus Erythematosus (SLE) patients with hipovitamin D.Methods: We performed an open clinical trial. Subjects were randomized into two different groups (supplementation or placebo) using simple random sampling. The treatment group got vitamin D3 softgel/ cholecalciferol 1200 IU/day or 30 mg/day, while the control group gotplacebo for 3 months. SLEDAI scores and FSS scores were calculated at pre and posttreatment.Results: There were 20 subjectsfor supplementation group and 19 subjects in the placebo group. From this study, before and after treatment, we found a significant difference of mean level of vitamin D in supplementation group (p=0.000), and no significant difference inpatients with placebo (p=0.427). Moreover, from the SLEDAI score analysis, observed a significant difference bothin the supplemented group (p=0.000) and the placebo group (p=0.006). FSS scores significantly different in the supplemented group (p=0.000). Incorrelation test,there was a negative correlation (r=-0763) between vitamin D level and disease activity (SLEDAI), and both showing stastistical significance between thepre supplementation (p=0.000) and post supplementation (r=-0846; p=0.000). Similarly to theFSS scores, there was a meaningfulnegative correlation (r=-0.931, p=0.000) between the level of vitamin D with FSS scores pre and post supplementation (r=-0.911; p= 0.000). Furthermore, there was a significant correlation between disease activity (SLEDAI) pre supplementation with fatigue condition pre supplementation (r=0.846; p = 0.000) and postsupplementation (r=0.913; p= 0.000).Conclusion: The supplementation of vitamin D 1200 IU per day in patients with SLE improve disease activity and degree of fatigue. Keywords: vitamin D, disease activity, fatigue, SLE